Crystal Structure of the Carbohydrate Recognition Domain of the Human Macrophage Galactose C-Type Lectin Bound to GalNAc and the Tumor-Associated Tn Antigen - Gabba, Adele (2022)
12/IA/1398 16/IA/4419 GOIPG/2016/858 IF/00780/2015 PTDC/BIA-MIB/31028/2017 UIDB/04378/2020 PD/BD/142847/2018 RTI2018-094751-B-C22 RTI2018-099592-B-C2.